FAKTOR RESIKO PERILAKU KEBIASAAN HIDUP YANG BERHUBUNGAN DENGAN KEJADIAN GAGAL GINJAL KRONIK - Jaya Firmansyah (Yayasan Pendidikan Medika Indonesia, 2022)
Chronic kidney disease is a functional and structural damage to the kidneys characterized by decreasing in the glomerular filtration rate (GFR) <60ml/min/1.73m2 that has lasted more than three months and is irreversible. The prevalence of chronic kidney failure continues to increase every year and the death rate for failure also increases. Medical expenses incurred by insurance institutions also continue to grow along with the increase in the number of sufferers and is the second highest funding order for treatment borne by Badan Pengelola Jaminan Sosial (BPJS) Kesehatan. Chronic kidney disease can be caused by certain disease conditions such as hypertension, diabetes, urinary tract infections, urinary tract stones, systemic lupus erythematosus, chronic pyelonephritis, chronic glomerulonephritis, polycystic kidney disease. Behavior of daily living such as smoking, high protein intake, consuming herbal medicine, use of analgesic drugs, high fat intake, consumption of high salt intake have a relationship and risk of chronic kidney disease.